2016
DOI: 10.1111/etap.12146
|View full text |Cite
|
Sign up to set email alerts
|

To Be or Not to Be: How Family Firms Manage Family and Commercial Logics in Succession

Abstract: We draw on the institutional logics perspective to understand different approaches that family firms can use to manage the process of succession. Based on the analysis of 21 case studies of family firms in Germany, we identify four different ways of managing potentially conflicting family and commercial logics that are associated with four different succession processes. Our findings contribute to the family firm literature by improving our knowledge of the heterogeneity of family firms and by explaining diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 71 publications
6
92
1
1
Order By: Relevance
“…For instance, family standing attributes correspond to a family logic and managerial competence attributes correspond to a business logic. Therefore, in line with Jaskiewicz et al (2015) findings, our empirical research suggests that incumbents have to address different logics in their decision to nominate the future successor. Moreover, our findings also extend previous empirical literature on CEO nomination processes (e.g., Bennedsen et al 2007;Bocatto et al 2010;Fang et al 2015).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…For instance, family standing attributes correspond to a family logic and managerial competence attributes correspond to a business logic. Therefore, in line with Jaskiewicz et al (2015) findings, our empirical research suggests that incumbents have to address different logics in their decision to nominate the future successor. Moreover, our findings also extend previous empirical literature on CEO nomination processes (e.g., Bennedsen et al 2007;Bocatto et al 2010;Fang et al 2015).…”
Section: Resultssupporting
confidence: 79%
“…Unlike other studies (i.e., Fang et al 2015) we attempt to understand the incumbent's intention as an ex-ante situation, which could be the antecedent of effective behavior, instead of the successor's nomination as an ex-post situation (after the decision is taken). Additionally, in line with Jaskiewicz et al (2015) findings, our research offers empirical evidence of the existence of different logics (family and business) that can influence, at minimum, the future successor nomination decision. Second, our proxy variable for SEW preservation helps to shed light on how factors such as the number of family members working in the firm can change the incumbent's reference point when nominating a family or a non-family member.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, both family logics and business logics affect family business goal selection (Jaskiewicz et al . ; Reay et al . ).…”
Section: Review Of Family Business Goals Literaturementioning
confidence: 99%
“…We indicated that in academia the institutional logic of research commercialization has joined the long‐prevalent institutional logic of open science. Scholars have noted that while two or more institutional logics may exist at the same time, they oftentimes compete, as they place different demands on the individuals exposed to them (Jaskiewicz et al, ; Reay and Hinings, ; Souitaris et al, ). Our results do not indicate that the open‐science logic prevalent in the studied research organizations has implications for researchers’ entrepreneurial intentions.…”
Section: Discussionmentioning
confidence: 99%